The Use Of Gis In Estimating Rain Fall Erosivity Factor Of Onkaparinga Watershed- South Australia - Trias Rahardianto (Prokons: Jurnal Teknik Sipil, 2013)
The study is aimed at the examination of spatial distribution of rainfall to produce rainfall erosivity map in Onkaparinga watershed, utilising Geographic Information System (GIS). Rainfall data was obtained from rainfall stations in and around the watershed as monthly precipitation data. Ordinary least square (OLS) method implemented to observe the relationship between rainfall erosivity as dependent variable, and both of rainfall and elevation as the explanatory variable. To create the continous surface of the site specific monthly and annual average precipitation data, the universal kriging interpolattion was implemented. The regression model shows that 96% of the predicted R factor value matches the observed R factor value. The result of this study is characterised the rainfall on the watershed as high temporal variability.Keywords: GIS, DEM, Universal kriging, OLS, Rainfall erosivity